Opening Address - Bode Florin (E3S Web of Conferences)
The 9th edition of the EENVIRO Conference (EENVIRO 2024) EU-CONEXUS EENVIRO Research Conference Bucharest, was held on 28 October - 01 November 2024, at Technical University of Civil Engineering Bucharest, bringing together researchers, practitioners, industry experts, and policy makers to discuss recent developments, emerging trends, and innovative solutions in environmental engineering and sustainable development. Throughout the conference, we explored cutting-edge research on energy efficiency, green building technologies, resource management, and climate resilience—core areas central to the EENVIRO mission of promoting a smarter and greener future.